Performance Measurement of Travel Agencies in Nigeria - Olaleye, Oluwafemi (Eastern Mediterranean University EMU, 2017)
In decision making, performance measurement is conducted to know how well the activities of the organization have enhanced successes, showing whether they are satisfactory, favorable or unfavorable to rendering services. Performance measurement assumes the same measure of importance for travel agencies and holds a very imminent role in its entire management processes. With the current situation of things in the industry, the increased mobility has brought about increased demand just as it has given rise to competition among travel agencies, who hold the responsibility of providing customers with services to move from one place to another. Amidst this scenario, the agencies strive to provide services that will best satisfy the expectations of customers and there are several others involved in this highly competitive business venture. Travel agency as intermediaries offer lucrative services and this is the reason performance measurement is necessary. It is in this light that this study on performance measurement in travel agencies in Lagos state was conducted to assess its influence on the decision making about service delivery. As a result, one hundred and thirty-eight (138) employees of eighteen travel agencies provided responses to the field survey conducted for this study. The study found that efficacy and value of performance measurement in the operations of travel agencies is entrenched in the outcome of performance information. The findings further revealed the employees in the travel agencies understand the relevance of and conduct performance measurement on as often as possible. This implies that performance information is useful for travel agencies, and effective for ensuring the successful service delivery, achieving profit objective, ensuring customer satisfaction, and to also attain global standards for travelers. Therefore performance measurement has a clear-cut relationship with service delivery, and the frequency at which travel agencies measure their performance gives rise to the productivity they experience in their operations. Keywords: Performance Measurement, Travel Agency, Nigeria.

ÖZ: Karar verirken, performans ölçümünde organizasyonların faaliyetlerinin ne kadar başarılarını artırdıpını bilerek, bize hizmet sunumunun tatmin edici, olumlu veya olumsuz olup olmadığını göstermektedir. Performans ölçümü, seyahat acenteleri arasında aynı oranda bir öneme sahiptir ve tüm yönetim süreçlerinde çok önemli bir rol oynar. Sektördeki mevcut durumu düşünürsek, artan mobilite (hareketlilik) talebi artırmakla birlikte seyahat acenteleri arasında rekabetle beraber müşterileri bir yerden bir yere taşımak için hizmet sunumluluğunu da beraberinde getirmiştir. Bu senaryo içerisindeacenteler daha iyi bir hizmet için çaba göstererek en iyi şekilde müşterilerin beklentilerini tatmin ederek bunların yanında son derece rekabetci iş girişiminde yer alan birkaç işletme vardır. Aracı olarak seyahat acentesi karlı hizmetleri sunuyor ve bu nedenle perfomans ölçümü gereklidir. Bunların ışığında Lagos eyaletindeki seyahat acentelerinde yapılan performans ölçümü üzerinde yapılan bu çalışma, hizmet sunumunda karar verme üzerindeki etkisini değerlendirmek için yapıldı. Bunun sonucunda toplam 18 seyahat acentesinden çalışan 138(yüz otuz sekiz) kişi üzerinde yapılan saha araştırmasından yanıtları vardır. Bu çalışma etkinliği ve seyahat acentelerinin çalışmalarındaki performans ölçümünün, seyahat ecetelerine karşılıklı hizmetin sonucunda çalışanların performans ölçümünü mümkün olduğunca önemseyerek gerçekleştirdiklerini ortaya koydu. Bu bulgular seyahat acentelerinde çalışaların performans ölçümünü mümkün olduğunca önemsediğini ve performans ölçümünü mümkün olduğunca çabuk gerçekleştirdiklerini ortaya koymuştur. Bu performans bilgilerinin seyehat acenteleri için yararlı olduğunu ve başarılı hizmet sunumunun sağlaması, kar amacı güden müşteri memnuniyetini sağladığı ve seyahat edenler için küresel standartlara v ulaşmasınI sağlamaktadır.bu performan ölçümünün hizmet sunumu ile açık uçlu bie ilişki içerdiğini ve seyehat acentelerinin performanslarını ölçme sıklığı faaliyetlerinde verimliliği deneyimliyorlar. Anahtar kelimeler: Performans Ölçümü, Seyahat Acentası, Nijerya
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2017. Supervisor: Assist. Prof. Dr. Mine Haktanır.
Keywords: Tourism; Tourism-Travel Agencies-Nigeria; Performance Measurement; Travel Agency; Nigeria